2004
DOI: 10.1074/jbc.m407958200
|View full text |Cite
|
Sign up to set email alerts
|

Leishmania major Elongation Factor 1B Complex Has Trypanothione S-Transferase and Peroxidase Activity

Abstract: In the Trypanosomatidae, trypanothione has subsumed many of the roles of glutathione in defense against chemical and oxidant stress. Crithidia fasciculata lacks glutathione S-transferase, but contains an unusual trypanothione S-transferase activity that is associated with eukaryotic translation elongation factor 1B (eEF1B). Here we describe the cloning, expression, and reconstitution of the purified ␣, ␤, and ␥ subunits of eEF1B from Leishmania major. Individual subunits lacked trypanothione S-transferase acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(29 citation statements)
references
References 61 publications
0
28
0
1
Order By: Relevance
“…No glutathione peroxidase activity was detectable in ElfA preparations. Interestingly, Vickers et al [12] have shown that the intact eEF1B complex is necessary for peroxidase activity found in the eEF1Bc subunit of Leishmania major eEF1B. Microarray analysis of A. fumigatus gene expression has revealed that ElfA (termed elongation factor-1c) expression is up-regulated twofold within 1 h of a temperature shift (30-48°C) which suggests a role for ElfA in protecting against heat shock [33].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No glutathione peroxidase activity was detectable in ElfA preparations. Interestingly, Vickers et al [12] have shown that the intact eEF1B complex is necessary for peroxidase activity found in the eEF1Bc subunit of Leishmania major eEF1B. Microarray analysis of A. fumigatus gene expression has revealed that ElfA (termed elongation factor-1c) expression is up-regulated twofold within 1 h of a temperature shift (30-48°C) which suggests a role for ElfA in protecting against heat shock [33].…”
Section: Discussionmentioning
confidence: 99%
“…However, GST-like domains have also been detected in distinct proteins such as Ure2p, Mak16, and EF1Bc (a subunit of the EF1B complex) [11]. Furthermore, although GST activity has recently been ascribed to the elongation factor protein complex EF1B isolated from rice and trypanothione S-transferase activity detected in EF1B complex from Leishmania major, no detection of GST activity in native EF1Bc has been possible [12]. In an attempt to purify the GST proteins (GstA-C) from A. fumigatus, glutathione (GSH)-Sepharose affinity chromatography was employed.…”
mentioning
confidence: 99%
“…This protein though, is involved in protein synthesis, has not been characterized in Leishmania species. The proteins of a similar family, EL-1a, EL-1B, and EL-4a, have been reported in various Leishmania species (14,28,29). Of these, EL-1a, cloned and characterized in L.donovani (29), has been attributed to have an essential role in survival and thus can serve as a good drug target (30).…”
Section: Discussionmentioning
confidence: 99%
“…Considerable evidence has suggested that nonselenium GSH peroxidase-like enzymes in trypanosomatids metabolize fatty acid and phospholipid hydroperoxides (56), although the activity is very low compared to that of selenium-containing GSH peroxidase. Leishmania also possess trypanothione S transferase activity associated with the eukaryotic translation elongation factor 1B, which reacts preferentially with linoleic acid hydroperoxide but not with H 2 O 2 (54). Recent reports also demonstrate that overexpression of APX within Leishmania and T. cruzi is more resistant to exogenously added H 2 O 2 (18,57).…”
mentioning
confidence: 88%